2019
DOI: 10.1080/14786419.2019.1656630
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and their biological activities from the roots of diospyros filipendula

Abstract: Phytochemical investigation of Diospyros filipendula (Ebenaceae) resulted in the isolation of eighteen compounds. Their structures were identified by analysis of mass spectrometric and spectroscopic (IR, 1D and 2D NMR) data. We report three benzoic acid derivatives (1-3), one peptide (4), one coumarin (5), three phthalides (6-8), three steroids (9-11) and seven triterpenes (12-18). Nine compounds (1, 4-8, 10, 17 and 18) are reported from the Ebenaceae family for the first time while the other nine are new to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…All of them gave a positive result for Liebermann-Burchard test, implying the triterpenoid or steroid nature. Analysis of their 1 H-and 13 C-NMR spectral data, confirmed by comparison with the previously reported values [6 -10], revealed that the isolated compounds were all pentacyclic triterpenoids. Compounds 1 and 2 were identified as friedelin [6] and epifriedelanol [6] of the friedelane type, and 3 -6 as lupeol [7], betulin [8], betulinic acid [9] and betulinaldehyde [10] of the lupane type, respectively.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…All of them gave a positive result for Liebermann-Burchard test, implying the triterpenoid or steroid nature. Analysis of their 1 H-and 13 C-NMR spectral data, confirmed by comparison with the previously reported values [6 -10], revealed that the isolated compounds were all pentacyclic triterpenoids. Compounds 1 and 2 were identified as friedelin [6] and epifriedelanol [6] of the friedelane type, and 3 -6 as lupeol [7], betulin [8], betulinic acid [9] and betulinaldehyde [10] of the lupane type, respectively.…”
Section: Resultssupporting
confidence: 74%
“…The carbon signal due to the methyl group at C-4, the most upfield signal, was observed at δ 11.6 (C-23). This signal was significantly more downfield than the corresponding signal in the 13 C-NMR spectrum of 1 owing to the different substituents at C-3.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations